Knowledge and practice of emergency contraception among female students of public university of Ouagadougou, Burkina Faso, West Africa - Sawadogo, Yobi A lexis; Ouedraogo, Issa; Kiemtore, Sibraogo; Ouedraogo, Fatou; Toure, Boubakar; Ouattara, Adama; Kain, Dantola Paul; Marie Ouedraogo, Charlemagne R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Female students are exposed to unsafe sex, sources of unwanted pregnancy and abortions. It is recognized that emergency contraception can effectively prevent pregnancy. The purpose of this study was to evaluate the knowledge and practices of Ouagadougou public university students in relation to emergency contraception in order to propose solutions to reduce the proportion of unwanted pregnancies among female students. Methods: This was a cross-sectional study conducted between May 1st and October 31st, 2016 in the public universities of Ouagadougou. A questionnaire was administered to a sample of 732 students randomly selected. Results: The average age of female students was 22.7 years old. The age group 19 to 24 was the most represented (68.03%). Of the students surveyed, 87% knew or had heard of emergency contraception. The students only used the emergency contraceptive pill. The emergency contraceptive use rate was 44.42%. Approximately, 83% of users were aware of the delay in using emergency contraception. The reasons for using emergency contraception were condom breakage (25.10%) and unprotected sex (74.9%). Female students purchased the contraceptive directly in pharmacies (93.61%). Conclusions: Emergency contraception gives women a last chance to avoid an unwanted pregnancy after unprotected sex. Awareness and free availability of emergency contraception (EC) could improve the reproductive health of female students.